Relationship Between Chronic Intermittent Hypoxia and Intraoperative Mean Arterial Pressure in Obstructive Sleep Apnea Patients Having Laparoscopic Bariatric Surgery. Issue 2 (April 2016) - Turan, Alparsian; You, Jing; Egan, Cameron; Fu, Alex; Gazmuri, Ignaxia; Khanna, Ashish; Eshraghi, Yashar; Ghosh, Raktim; Bose, Somnath; Qavi, Shahbaz; Arora, Lovkesh; Sessler, Daniel I.; et al.
Abstract : Surv Anesthesiol 2016;60(2):59–60 Patients with obstructive sleep apnea (OSA) present with chronic enhancement in sympathetic adrenergic activity, one of the main mechanisms in the development of cardiovascular morbidity in these patients. Recurrent nocturnal hypoxemia in OSA also decreases baroreceptor sensitivity and weakens peripheral vascular responses to adrenergic signals.